Given the equation:
![y=5\sqrt[]{x}+5](https://img.qammunity.org/2023/formulas/mathematics/college/725xgsykc0ptzkvkeuqa27ii20y3vrj505.png)
Let's transform the equation above.
1. A horizontal shift of 5 units the the right:
y = (5√x -5) + 5
y = (5√x -5) + 5
2. A stretch by a factor of 4:
Here a vertical stretch occcured.
y = 4(5√x -5) + 5
y = 4(5√x - 5) + 5
Therefore, the transformed equation is:
![y=4(5\sqrt[]{x-5})+5](https://img.qammunity.org/2023/formulas/mathematics/college/t4vymkpzc6yvd7nz3vnnu5g77ze8mrluj3.png)
![y=20\sqrt[]{x-5}+5](https://img.qammunity.org/2023/formulas/mathematics/college/vli89gzaf5p1hkksbdmf4gq8m57sqntidv.png)